Oxidation of Diarylthiocarbamides with Lead Tetraacetate - Chattree, N.S.; Bhardwaj, A.; Sharma, T.C. (Asian Journal of Chemistry, 2012)
Oxidation of a series of diarylthiocarbamides with lead tetraacetates has been carried out leading to the formation of corresponding S-acetoxy-diarylthiocarbamides.